Unveiling Luxury Consumption Intention in Scarcity: The Role of Locus of Control and Economic Mobility Perceptions - Yuejun Liu; Banggang Wu; Xiaoyu Deng (Journal of Theoretical and Applied Electronic Commerce Research)
Perceived scarcity can significantly shape consumer behavior, particularly regarding luxury consumption during economic downturns. This study examines how perceived scarcity influences the preference for luxury goods and assesses the mediating role of perceived control in this relationship. Employing a multi-method approach that combines questionnaire surveys and bias adjustment techniques, this research captures the complex interplay between scarcity cues, perceived control, and consumption behaviors. The findings indicate that when consumers experience scarcity, they are more inclined to seek out luxury goods as a means to restore a sense of psychological balance. Perceived control emerges as a key mediating factor, helping explain why scarcity leads to a heightened interest in luxury products. This mediation suggests that consumers turn to luxury items not solely due to external constraints, but also as a way to reassert control over their circumstances. By integrating compensatory control theory and considering variations in locus of control and perceived economic mobility, this study provides a nuanced understanding of the psychological mechanisms underpinning luxury consumption in resource-constrained contexts. These insights advance theoretical perspectives on scarcity effects and offer practical implications for marketers and policymakers aiming to engage consumers responsibly and effectively in challenging economic environments.